Małe analizy. Etiudy w PWSFTviT - Kolski, Jan Jakub (Wydawnictwo Naukowe UAM w Poznaniu; Wydawnictwo PWSFTViT w Łodzi, 2012)
Performing as a lecturer and artistic tutor of students’ etudes requires creation of a common platform for discussion and constructive criticism. The above text is an example of didactic pact between the teacher and the student. Analysis of the Rafał Skalski etude Żeby nie było niczego is also an excuse to discuss the composition, construction of the characters and acting roles, as well as so-called "Zatorski spiral", interpretation of ‘becoming’ and truth in dialogue. Discussed scenes of the etude allow to understand the importance of internal tension – a kind of punctum – creating a dramatic and visual potential of the film.

Występowanie w roli wykładowcy i artystycznego opiekuna przy omawianiu etiud studenckich, wymaga stworzenia wspólnej platformy do dyskusji i konstruktywnej krytyki. Powyższy tekst jest przykładem dydaktycznego paktu między nauczycielem i uczniem. Analiza etiudy Rafała Syski „Żeby nie było niczego” jest także pretekstem do dyskusji na temat kompozycji, budowy postaci i odgrywania ról aktorskich, jak również tak zwanej "spirali Zatorskiego", interpretacji „stawania się „ i prawdy w dialogu. Omówione sceny etiudy pozwalają zrozumieć znaczenie wewnętrznego napięcia – rodzaj punctum – tworząc dramatyczny i wizualny potencjał filmu.
Little tiny analysis. Etudes in The Polish National Film, Television and Theatre School
Jan Jakub Kolski, PWSFTviT w Łodzi, Małe analizy. Etiudy w PWSFTviT, Little tiny analysis. Etudes in The Polish National Film, Television and Theatre School, „Images” 2012, vol. X: Microcosmos, red. A. Szpulak i W. Otto, nr 19, s. 113-120, ISSN 1731-450x, język: polski
Keywords: Film/etudes; analysis; film composition; Zatorski spiral; construction of the film character; film/etiudy; analiza; kompozycja filmu; spirala Zatorskiego; konstrukcja postaci filowej